The history of vaccines 2 - Rees, Anthony R. (Henry Stewart Talks, 2023)
The history of measles, Measles and herd immunity, The discovery of measles virus, Vaccine development, The reasons for measles vaccine hesitancy, The history of tuberculosis (TB), TB is a dangerous widespread bacterial disease, Vaccine developed for children, Antibiotic solutions for adults, The history of Poliomyelitis, The discovery of the virus, Pathogenesis and vaccines, The mixed world of polio vaccination